Pengamatan Kondisi Mikroskopik dan Usaha Untuk Menghilangkan Bakteri Filamentous dengan Penambahan Klorin pada PT. X Industri Kertas di Jawa Timur - Oris Hatpa Aditya Azhar; Rizka Novembrianto (Yayasan Literasi Sains Indonesia, 2023)
One type of industry that can cause water pollution is the paper industry. In order to reduce liquid waste for the environment, waste water treatment is carried out. Bacteria are widely used for various food and non-food production processes. Filamentous bacteria or also called filamentous bacteria are the abnormal growth of certain bacteria, such as Escherichia coli. The type of research used for this research is research with quantitative methods. Quantitative research method is a type of research that has specifications in a structured, planned and systematic way, starting from the beginning to the manufacturing process of the research design. In this study, using the addition of 0.5% chlorine solution at a dose of 5 ppm, and using 5 days The parameter tests in the aeration tank: DO, pH, MLSS, SVI, Filamentous Microscopic Conditions and parameter tests in the effluent bath: DO, pH, TSS, COD, Turbidity. From the research that has been done, the results obtained in the aeration tank with the pH parameter having an average value of 8.02, DO having an average value of 6.31, MLSS with an average of 3586, and SVI of 135. Results in the effluent bath parameter pH has an average of 7.83,. DO has an average value of 3.04, turbidity has a value of 10.7-76 on the fifth day, COD value has an average value of 168, and TSS value has an average value of 121.5.